Osteoporosis and fracture after gastrectomy for stomach cancer: A nationwide claims study. Issue 17 (April 2018) - Seo, Gi Hyeon; Kang, Hae Yeon; Choe, Eun Kyung
Abstract : Abstract: This study was planned to evaluate the incidence and risk factors of osteoporosis and fracture after gastrectomy for stomach cancer using a nationwide claims database in South Korea. Data from 41, 512 patients (50–79 years) who underwent gastrectomy for stomach cancer from 2008 to 2010 with at least 5 years of follow-up were obtained from the Health Insurance Review and Assessment Service database. Patients diagnosed with osteoporosis and prescribed bisphosphonate or raloxifene or who experienced osteoporotic fractures after gastrectomy were operationally defined as osteoporosis. Osteoporotic fracture was defined as a fracture at common osteoporotic fracture sites (spine, pelvis, hip, forearm, or rib). In total, 37, 076 patients were included in the final analysis. The incidences of postgastrectomy osteoporosis and osteoporotic fractures were 41.9 and 27.6 cases per 1000 person-years, respectively. Multivariate analysis showed that older age (hazard ratio [HR] 1.88; 95% confidence interval [CI] 1.79–1.96), female gender (HR 2.46; 2.35–2.58), total gastrectomy (HR 1.10; 1.04–1.16), and diabetes (HR 1.16; 1.11–1.22) were significantly associated with osteoporosis and that older age (HR 1.90; 95% CI 1.80–2.01), female gender (HR 1.50; 1.41–1.58), total gastrectomy (HR 1.17; 1.10–1.25), chemotherapy (HR 1.06; 1.00–1.12), and diabetes (HR 1.26; 1.19–1.33) were significantly associated with fractures. Osteoporotic fractures occurred a median 3.1 years after gastrectomy. Among the 5175 fracture patients, 780 (15.1%) experienced multisite fractures, mostly in the elderly and chemotherapy groups. The osteoporosis and osteoporotic fracture incidences are high in patients within a relatively short timeframe after gastrectomy for stomach cancer. Systematic management of osteoporosis is necessary after this surgery.